Inventarisasi Gulma di Beberapa Lahan Perkebunan Rakyat, Jawa Timur: Inventory of Weeds on Smallholder Farmers Land, East Java - Tarigan, Puji Lestari (Agrocentrum, 2024)
Plantation crops are plants that can be cultivated for many years to come. East Java has numerous plantation crops, including apples, guava, oranges, cocoa, moringa, and sugarcane. Wild plants are commonly found around crops in plantation areas. Plantation crops are at risk from biotic disturbances caused by these plants, which requires adequate management. Knowing the dominant weeds in the region allows for effective control. Weed dominance is measured using a species IVI (Importance Value Index). The purpose of this study is to investigate how weeds spread throughout each plantation area. The quadrat technique is used to manage inventories. Three samples are collected from each land and measured according to a formula. The dominant weeds in each plantation land are as follows: apple=Cyperus rotundus, guava=Parietaria judaica, orange=Mikania scandens, cocoa=Persicaria odorata, moringa=Muhlenbergia schreberi, and sugarcane=Dactylotenium aegyptium. Control is based on weed groups, namely broad-leaved (Parietaria judaica, Mikania scandenes, and Persicaria odorata), as well as narrow-leaved (Muhlenbergia schreberi), and nutsedge (Cyperus rotundus). Weeds in the land may threaten crops, thus it must be managed. Controls have to conform to its principles so that they may be carried out properly and efficiently.